Kajian Pertumbuhan Ikan Tembakang (Helostoma temminckii) Di Rawa Bawang Latak Kabupaten Tulang Bawang, Lampung - Bintang Ubamnata; Rara Diantari; Qadar Hasani (Jurnal Penelitian Pertanian Terapan, 2015)
Tembakang Fish (Helostoma temminckii) is one of the fish that have high economic value in Rawa Bawang Latak. Overfishing and the introduction of fish resulted tembakang number of fish populations decline, so it takes the efforts of domestication. This study aims to determine the growth pattern that includes tembakang fish length and weight relationships, growth parameters, and factor conditions. Research carried out for four months, ie in October 2013 - January 2014. Tembakang fishing done at two stations in Rawa Bawang Latak. The sampling frequency of fish is done only once a month using Sero. The results showed that the pattern of growth tembakang fish is allometric positive, condition factor values male and female fish were not significantly different, female tembakang fish growth faster than the male fish, fish tembakang males on the size of 180.6 mm was 21 months, while females in size 191.1 mm 8 months old. Keywords: Tembakang, Growth, Sero, Rawa Bawang Latak.